THE EFFECT OF LEARNING MOTIVATION ON ACADEMIC ACHIEVEMENT OF LINEAR ALGEBRA MATERIAL USING MOBILE MATLAB - Restu Lusiana; Reza Kusuma Setyansah (Prodi Pendidikan Matematika FKIP Universitas Madura, 2023)
The purpose of this study was to determine whether or not there is a relationship between learning motivation and student academic achievement using mobile Matlab. This research was conducted at Universitas PGRI Madiun referring to the measurement of the results of student learning motivation using mobile Matlab on linear algebra material. The method used in this research is the survey method with correlation technique. The use of these methods aims to determine the amount of influence and impact of student learning motivation using mobile Matlab on the acquisition of academic achievement in linear algebra material. The population in this study involved 25 students with a purposive sampling technique. The Likert scale used in learning motivation is a tool used in this study as an instrument. Exposure of data from the calculation of 25 items of questionnaire learning motivation by using Matlab mobile then obtained reliability results with Cronbach's Alpha of 0.853 (consistent) and the validity results on all items above the calculated r-table of 0.195 then declared valid. The results of this study, have a positive relationship between student learning motivation using mobile Matlab on academic achievement. However, it appears that learning motivation has a role level of 55.20% on learning achievement and the rest is due to the impact of the influence of variables not examined in this study.